Virtualization of information as the direction of development of accounting support systems. Empirical evidence from Poland - Bauer, Kinga; Baran, MichaÅ‚ (International Journal of Accounting and Economics Studies, 2015)
A significant trend observed recently in shaping the communication condition between economic entities, and the authorities is the growing virtualization of information circulation. The aim of this article is to examine the attitudes and expectations of specialists (employees of accounting offices) towards the process. Opinions of the specialists and accounting community members were collected as part of a survey, in which the respondents came from the southern Polish territory. This location was chosen due to a particularly high rate of change to the location, which in turn made the respondents more sensitive to the issue. 114 interviews had been collected, which were then subjected to statistical analysis. The outcome, in the most general terms, indicates a generally positive attitude of the respondents towards the occurring phenomenon.